Pengaruh Etos Kerja, Komunikasi Internal, Terhadap Kinerja Pegawai dengan Komitmen Kerja sebagai Variabel Intervening - Maulidya Handayani Suita Putri; Risambessy, Agusthina; Chandra, Felix (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2024)
This research discusses the influence of work ethic, internal communication, on employee performance with work commitment as an intervening variable at the Central Maluku Regency Personnel and Human Resources Development Agency (BKPSDM) Office. This research was conducted using a questionnaire distributed using a saturated sampling technique with a sample size of 47, the analytical method used in this research was Partial Least Square (PLS). Based on the results of the analysis it can be seen that, 1) work ethic has a significant effect on employee performance, 2) work ethic does not have a significant effect on work commitment, 3) work commitment has a significant effect on employee performance, 4) internal communication has a significant effect on employee performance, 5) internal communication has a significant effect on work commitment, 6) work ethic does not have a significant effect on employee performance through work commitment, 7) internal communication has a significant effect on employee performance through work commitment.